Super-transparent super-heat-insulation light silicon dioxide aerogel material as well as preparation method and application thereof
The pore structure of silica aerogel is reconstructed through pinhole drying technology, combined with solvent replacement and super-proto-drying, the problem of deterioration of thermal insulation performance of silica aerogels at high temperatures in the prior art is solved, and the high efficiency of thermal insulation and transparency is greatly improved.
Patent Information
- Application Number
- CN202411831174.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The thermal insulation performance of existing silica aerogel materials deteriorates at high temperatures, and the randomness of nanoparticle accumulation reactions in alcohol gels leads to a wide distribution of pore structures, affecting thermal insulation and light transmission properties.
The alcohol gel pore structure reconstruction method based on pinhole drying is adopted to eliminate macropores through post-treatment to achieve homogenization of the pore structure. Combined with ethanol solvent replacement and supercritical drying, ultra-transparent ultra-heat-insulated lightweight silica aerogel material is prepared.
The thermal insulation performance and light transmittance of the aerogel are significantly improved. The room temperature thermal conductivity is at least 0.010W/(m·K). The thermal conductivity increases slightly at 100°C, with a light transmittance reaching 93.8%, and a haze as low as 1.2%.
Smart Images

Figure CN119637885A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanoporous materials, and in particular to an ultra-transparent, ultra-insulating, lightweight silica aerogel material and a preparation method and application thereof. Background Art
[0002] Silica aerogel is a porous network structure composed of nano-silica colloidal particles stacked in space. It is a lightweight solid material. As the most typical representative of the aerogel family, silica aerogel is also the most mature and widely used type of oxide aerogel. This material has shown application prospects in many fields such as space exploration, thermal insulation, new energy power batteries, environmental protection, analysis and detection, high-efficiency catalysis and high-energy physics. It is praised as one of the ten magical materials that change the world. Silica aerogel has many excellent properties such as light weight, high specific surface area, large porosity, transparent optics, and super thermal insulation. Due to the nanoporous characteristics, the thermal conductivity of silica aerogel composite materials can be as low as 0.012W / (m·K) at ambient temperature and atmospheric pressure, showing excellent thermal insulation properties.
[0003] Compared with general thermal insulation materials, silica aerogel composite materials have been proven to be reliable and effective in thermal insulation under complex application environments such as different temperature ranges, different air pressures, and different atmospheres. They are not only applicable to ground normal pressure environments, but also more effective than traditional multi-layer thermal insulation materials in low vacuum environments such as Mars, Saturn, and the intermediate layer of near-space. They are also particularly applicable to high vacuum environments such as the moon, low-Earth orbit, and the stratosphere, and where there is a demand for load-bearing. For all thermal insulation materials, including aerogels, thermal insulation performance directly affects the thickness and weight of the laid thermal insulation layer. Therefore, reducing thermal conductivity is of the most essential significance for reducing the weight and increasing the efficiency of the system, especially for efficient thermal insulation in certain harsh confined spaces and applications with high sensitivity to weight. It is the decisive factor in determining whether the material can be used.
[0004] Lightweight transparent silica aerogel is widely used in emerging fields with high demand for transparent heat insulation, such as solar thermal systems. Invention patent CN105271263A discloses a method for preparing transparent silica aerogel, which is prepared by mixing water and hexamethyldisiloxane in ethanol, adding hydrofluoric acid as a catalyst, heating the gel in a reactor, and supercritical drying to obtain a transparent aerogel with an apparent density of 100 mg / cm 3 The thermal conductivity at 25°C is as low as 0.012W / (m·K). Invention patent CN109019611A discloses a method for rapidly preparing bulk transparent silica aerogel, which uses an organic silicon source and aprotic polar solvent to prepare a bulk transparent aerogel with a density of 0.11g / cm 3, thermal conductivity is 0.013W / (m·K). Invention patent CN109179428A prepares an enhanced transparent silica aerogel, using organosilicon to in-situ generate monodisperse silica nanoparticles, and after drying, obtains an enhanced aerogel with a density of 0.11g / cm3, a thermal conductivity of 0.012W / (m·K), and a visible light transmittance of 90%.
[0005] However, due to the randomness of the nanoparticle stacking reaction in the sol-gel, the pore structure distribution in the alcohol gel is inevitably relatively wide, and there are a large number of large pores at the level of hundreds of nanometers, which has an adverse effect on the heat insulation and light transmission of the transparent aerogel, especially at relatively high temperatures. The thermal insulation performance deteriorates seriously. In response to this problem, the invention patent CN117699808A has developed a two-phase sol-gel method based on time and space separation and assisted by alkaline amino acids, which effectively divides the generation of sol and the formation of gel in time and space, and realizes that the silica nanoparticle skeleton and pore structure in the hydrogel are small enough and uniform enough, which solves this problem well. However, for the numerous alcohol gel systems prepared using silicone, there is also an urgent need for a simple and universal post-processing method to achieve the homogenization of the alcohol gel nanopores, so that the heat insulation and light transmittance of the aerogel finally prepared are greatly improved. Summary of the invention
[0006] In order to solve one or more technical problems existing in the prior art, the present invention provides an ultra-transparent, ultra-insulating, lightweight silica aerogel material and its preparation method and application. The present invention proposes a method for reconstructing the pore structure of alcohol gel based on pinhole drying, and eliminates the punching through post-processing to make the pore structure uniform. The room temperature thermal conductivity of the prepared high-efficiency, heat-insulating, lightweight, transparent silica aerogel is as low as 0.010W / (m·K). When the temperature rises to 100°C, the room temperature thermal conductivity of the aerogel increases slightly, which is only 0.012W / (m·K); the ultra-transparent, ultra-insulating, lightweight silica aerogel material with a thickness of 10mm has a light transmittance of 93.8% and a haze of 1.2% at 550nm.
[0007] In a first aspect, the present invention provides a method for preparing an ultra-transparent, ultra-insulating, lightweight silica aerogel material, comprising:
[0008] (1) soaking a transparent silica wet gel having a silica solid content of 1 to 10% in a mixed alcohol solvent for solvent replacement to obtain a mixed alcohol gel; wherein the mixed alcohol solvent is composed of lower alcohols and higher alcohols with different molecular weights;
[0009] (2) placing the mixed alcohol gel on a separation net in a pinhole drying device, and injecting the mixed alcohol solvent into the pinhole drying device until the mixed alcohol solvent contacts the mixed alcohol gel through the separation net, and sealing the pinhole drying device;
[0010] (3) volatilizing the mixed alcohol solvent in the pinhole drying device in a controllable manner until the volume of the mixed alcohol solvent no longer changes, thereby obtaining a transparent silica alcohol gel with pore reconstruction;
[0011] (4) The transparent silica alcohol gel with reconstructed pores is subjected to ethanol solvent replacement and supercritical drying in sequence to obtain an ultra-transparent, ultra-insulating and lightweight silica aerogel material.
[0012] Preferably, the transparent silicon dioxide wet gel has a silicon dioxide solid content of 2.5%.
[0013] Preferably, the lower alcohol is one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol; the higher alcohol is one or more of n-pentanol, isopentanol, n-hexanol, heptanol, octanol, ethylene glycol, and hexanetriol.
[0014] More preferably, the lower alcohol is ethanol; and the higher alcohol is n-pentanol.
[0015] Preferably, the volume ratio of the lower alcohol to the higher alcohol is (0.01-9):1.
[0016] More preferably, the volume ratio of the lower alcohol to the higher alcohol is 3:1.
[0017] Preferably, the pinhole drying device includes a container body, an isolation net and a container cover; the isolation net is fixed inside the container body to divide the pinhole drying device into an upper end area and a lower end area; the mixed alcohol gel is placed on the isolation net, and the mixed alcohol solvent is placed in the lower end area; a through hole is opened on the container cover, and an adjusting plate for adjusting the opening and closing of the through hole is provided on the container cover; when the adjusting plate controls the closing of the through hole, the container body and the container cover form a closed container.
[0018] Preferably, the diameter of the through hole is 200-500 μm; and the porosity of the container cover is 0.005-0.015%.
[0019] Preferably, in step (3): the pinhole drying device is placed in a ventilated environment, and controllable volatilization is performed by controlling the opening and closing degree of the through hole on the container cover, the wind speed of the ventilated environment and the ambient temperature.
[0020] Preferably, in step (3), the time of the controlled volatilization is 6 to 120 hours.
[0021] More preferably, in step (3): the time of the controlled volatilization is 48 hours.
[0022] Preferably, the volume of the pore-reconstructed transparent silica alcohol gel is 1 / 10 to 1 of that of the mixed alcohol gel.
[0023] More preferably, the volume of the pore-reconstructed transparent silica alcohol gel is 1 / 4 of that of the mixed alcohol gel.
[0024] Preferably, in step (4): the supercritical drying adopts supercritical carbon dioxide drying, the pressure in the drying kettle is maintained at 8-20 MPa, the temperature in the drying kettle is controlled at 10-25°C, and the circulating liquid carbon dioxide is used to maintain it for 24-120 hours, and then the temperature is increased to 40°C at a rate of 5-10°C / h to reach a supercritical state and maintained for 24-72 hours, and then the pressure is released to atmospheric pressure at a rate of 0.3-1 MPa / h.
[0025] In a second aspect, the present invention also provides an ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by any of the preparation methods of the first aspect above.
[0026] Preferably, the ultra-transparent, ultra-insulating, lightweight silica aerogel material has one or more of the following properties:
[0027] The density of the ultra-transparent, ultra-insulating, lightweight silica aerogel material is 0.06 to 0.15 g / cm3;
[0028] The ultra-transparent, ultra-insulating, lightweight silica aerogel material with a thickness of 10 mm has a light transmittance of 90.5-93.8% and a haze of 1.2-3.1% at 550 nm;
[0029] The thermal conductivity of the ultra-transparent, ultra-insulating, lightweight silica aerogel material is 0.010-0.014 W / (m·K) at room temperature and pressure, and the thermal conductivity is 0.012-0.017 W / (m·K) at 100° C. and pressure.
[0030] In the third aspect, the present invention also provides an ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by the preparation method described in the first aspect, which can be used in solar thermal collection systems, new generation space science, high energy physics, buildings or electronics for transparent thermal insulation, high energy particle capture, and other applications.
[0031] Compared with the prior art, the present invention has at least the following beneficial effects:
[0032] (1) The present invention proposes a pinhole drying device in the preparation method of ultra-transparent ultra-insulating lightweight silica aerogel material, in which the liquid in the pores of the mixed alcohol gel volatilizes at a controllable rate and to a controllable degree. Since the hydraulic pressure of the large pores in the mixed alcohol gel is smaller and the hydraulic pressure of the small pores is larger, the liquid in the large pores will volatilize first, causing the large pores to gradually become smaller more easily, and the content of the large pores of the mixed alcohol gel will be greatly reduced, so that the pores in the entire mixed alcohol gel become smaller and more uniform, and the volume of the mixed alcohol gel is also reduced, and finally a transparent silica alcohol gel with pore reconstruction is obtained. Then, the transparent silica alcohol gel with pore reconstruction is subjected to solvent replacement and supercritical drying to obtain an ultra-transparent ultra-insulating lightweight silica aerogel material. Since the nanopores constituting the aerogel are small and uniform in size, which are all smaller than the mean free path of gas molecules, the gas phase heat transfer of the aerogel is also very small, and the uniform small pores have little scattering of visible light, resulting in a high direct transmittance of light, and the aerogel is transparent and does not appear foggy.
[0033] (2) The present invention proposes a pinhole drying device, based on which the pore structure of the mixed alcohol gel is reconstructed, and a simple post-processing general strategy for eliminating large pores and making the pore structure uniform is proposed. This pore control strategy is applicable to transparent silica alcohol gel prepared by any method.
[0034] (3) The present invention uses a mixed alcohol solvent to achieve the volatilization of the liquid in the pores of the mixed alcohol gel at a controllable rate and a controllable degree, so that the mixed alcohol gel undergoes a controllable volume shrinkage and its integrity is retained. The final aerogel density can also be controlled according to actual needs in the later stage, without controlling the solid content in the sol-gel stage so that the final aerogel density is fixed and cannot be adjusted.
[0035] (4) The ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by the present invention has small nanopores, uniform pore distribution, and no macropores. On the one hand, the thermal insulation performance of the aerogel is regulated. The thermal conductivity of the aerogel at room temperature and at relatively high temperatures is very small. The lowest thermal conductivity at room temperature is only 0.010 W / (m·K). When the temperature rises to 100°C, the room temperature thermal conductivity of the aerogel increases slightly, which is only 0.012 W / (m·K), thereby achieving efficient thermal insulation over a wide temperature range. On the other hand, the optical transparency and transparent quality of the aerogel are optimized. Not only is the total light transmittance high, but the direct light transmittance is also high. The ultra-transparent, ultra-insulating, lightweight silica aerogel material with a thickness of 10 mm has a light transmittance of up to 93.8% at 550 nm and a haze as low as 1.2%. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 A flow chart of a method for preparing an ultra-transparent, ultra-insulating, lightweight silica aerogel material provided by one embodiment of the present invention;
[0038] Figure 2 A schematic structural diagram of a pinhole drying device provided by one embodiment of the present invention;
[0039] Figure 3 This is an appearance diagram of the ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared in Example 1;
[0040] Figure 4 This is a transmission electron microscope image of the ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared in Example 1;
[0041] Figure 5 This is a scanning electron microscope image of the ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared in Example 1;
[0042] Figure numerals: 20 - container body; 21 - isolation net; 22 - container cover; 221 - through hole; 222 - adjustment sheet. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0044] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing an ultra-transparent, ultra-insulating, lightweight silica aerogel material, the preparation method comprising:
[0045] (1) soaking a transparent wet silica gel having a silica solid content of 1 to 10% (e.g., 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%) in a mixed alcohol solvent for solvent replacement to obtain a mixed alcohol gel; wherein the mixed alcohol solvent is composed of lower alcohols and higher alcohols with different molecular weights;
[0046] (2) placing the mixed alcohol gel on an isolation net in a pinhole drying device, injecting a mixed alcohol solvent into the pinhole drying device until the mixed alcohol solvent contacts the mixed alcohol gel through the isolation net, and sealing the pinhole drying device;
[0047] (3) volatilizing the mixed alcohol solvent in the pinhole drying device in a controllable manner until the volume of the mixed alcohol solvent no longer changes, thereby obtaining a transparent silica alcohol gel with pore reconstruction;
[0048] (4) The pore-reconstructed transparent silica alcohol gel is subjected to ethanol solvent replacement and supercritical drying in sequence to obtain an ultra-transparent, ultra-insulating, lightweight silica aerogel material.
[0049] In an embodiment of the present invention, first, a pinhole drying device is proposed in the preparation method, in which the liquid in the pores of the mixed alcohol gel volatilizes at a controllable rate and a controllable degree. Since the hydraulic pressure of the large pores in the mixed alcohol gel is smaller and the hydraulic pressure of the small pores is larger, the liquid in the large pores will volatilize first, causing the large pores to gradually become smaller more easily, and the content of the large pores of the mixed alcohol gel will be greatly reduced, so that the pores in the entire mixed alcohol gel become smaller and more uniform, and the volume of the mixed alcohol gel is also reduced, and finally a transparent silica alcohol gel with pore reconstruction is obtained. Then the transparent silica alcohol gel with pore reconstruction is subjected to solvent replacement and supercritical drying to obtain an ultra-transparent, ultra-insulating, lightweight silica aerogel material. Since the nanopores constituting the aerogel are small and uniform in size, all of which are smaller than the mean free path of gas molecules, the gas phase heat transfer of the aerogel is also very small, and the uniform small pores have little scattering of visible light, resulting in a high direct transmittance of light, and the aerogel is transparent and does not appear foggy.
[0050] According to some more preferred embodiments, the transparent silica wet gel has a silica solid content of 2.5%.
[0051] In the present invention, it has been experimentally confirmed that if the silica solid content of the transparent silica wet gel is less than 1%, there are too many macropores in the wet gel, and its structural overlap is very poor, that is, the strength is poor, which will affect the thermal insulation performance of the prepared aerogel material; if the silica solid content of the transparent silica wet gel is higher than 10%, then after the pore reconstruction, the solid content of the obtained pore-reconstructed transparent silica alcohol gel is too high, and the density is relatively large at this time, thus resulting in increased solid-phase heat transfer, which in turn leads to poor thermal insulation performance of the final prepared aerogel material. Therefore, in order to ensure the thermal insulation performance of the final prepared aerogel material, the silica solid content of the transparent silica wet gel is limited to 1-10%.
[0052] According to some more preferred embodiments, the preparation method of transparent silica wet gel is as follows: 15.2g of methyl orthosilicate, 32g of methanol, 3.6g of water, and 10μL of dilute hydrochloric acid with a concentration of 0.1mol / L are added to a flask respectively, and after mixing by magnetic stirring, the temperature is raised to 70°C, and refluxed at this temperature for 8h; then the reflux device is changed to a distillation device, the temperature is raised to 100°C, and the methanol in the reaction solution is completely evaporated, and after the reaction is completed, it is cooled to room temperature to obtain a mixed solution; then a sufficient amount of acetonitrile is added to the mixed solution to make the total mass of the mixed solution 600g~60g (corresponding to the solid content of silica in the wet gel finally obtained of 1%~10%), and then ammonia water is added dropwise to the above mixed solution, and after stirring evenly, it is poured into the forming mold for gel, and then placed in a 60°C oven for drying for 48h, and the mold is taken out after cooling to obtain a transparent silica wet gel.
[0053] According to some more preferred embodiments, in step (1), a transparent silica wet gel having a silica solid content of 1 to 10% is immersed in an excess volume (5 to 10 times) of a mixed alcohol solvent for solvent replacement, and the process is repeated three times to obtain a transparent silica mixed alcohol gel (hereinafter referred to as mixed alcohol gel). In the present invention, by limiting the volume of the mixed alcohol solvent and the number of solvent replacements, it is possible to avoid using too much organic solvent and achieve sufficient solvent replacement, which is beneficial to maintaining a good physical shape of the aerogel finally prepared.
[0054] According to some preferred embodiments, the lower alcohol is one or more of methanol, ethanol, propanol, isopropanol, butanol, and isobutanol; the higher alcohol is one or more of n-pentanol, isopentanol, n-hexanol, heptanol, octanol, ethylene glycol, and hexanetriol.
[0055] It should be noted that several types refer to any two or more types mixed in any proportion. For example, lower alcohol is methanol, ethanol, and propanol mixed in any proportion.
[0056] According to some more preferred embodiments, the lower alcohol is ethanol; and the higher alcohol is n-pentanol.
[0057] According to some preferred embodiments, the volume ratio of the lower alcohol to the higher alcohol is (0.01-9):1 (for example, it can be 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.06:1, 0.1:1, 0.2:1, 0.3:1, 0.5:1, 0.6:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1 or 9:1).
[0058] According to some more preferred embodiments, the volume ratio of the lower alcohol to the higher alcohol is 3:1.
[0059] In the present invention, a mixed alcohol solvent consisting of a relatively small molecular weight lower alcohol and a relatively large molecular weight higher alcohol is selected, and the solvents inside the mixed alcohol gel and in the pinhole drying device where it is located during pore reconstruction are all mixed alcohol solvents. The purpose is to avoid cracks caused by the rapid volatilization of all the volatile lower alcohols in the initial stage of the mixed alcohol gel, and more importantly, to accurately control the residual amount of the higher alcohol with poor volatility, to ensure the volume shrinkage of the final mixed alcohol gel, thereby ensuring the density of the final aerogel. Experiments have confirmed that if the volume ratio of lower alcohol to higher alcohol is less than 0.01:1, the amount of lower alcohol is too small, and the amount of lower alcohol volatilized during the pore reconstruction process is small, so the pore reconstruction effect is poor; if the volume ratio of lower alcohol to higher alcohol is higher than 9:1, the amount of lower alcohol is too large, and a large amount of lower alcohol volatilizes too quickly during the pore reconstruction process, which will cause the structure of the mixed alcohol gel to be unstable, shrinking, deforming, etc., thereby destroying the structure of the transparent silica alcohol gel with pore reconstruction.
[0060] According to some preferred embodiments, Figure 2 As shown, the pinhole drying device includes a container body 20, an isolation net 21 and a container cover 22; the isolation net 21 is fixed inside the container body 20 to divide the pinhole drying device into an upper end area and a lower end area; the mixed alcohol gel is placed on the isolation net 21, and the mixed alcohol solvent is placed in the lower end area; a through hole 221 is opened on the container cover 22, and an adjusting piece 222 for adjusting the opening and closing of the through hole is provided on the container cover 22; when the adjusting piece 222 controls the closing of the through hole 221, the container body 20 and the container cover 22 form a closed container.
[0061] It should be noted that, in the present invention, the container body can be a coverless cylindrical shape, a coverless rectangular parallelepiped shape, etc. The container body and the isolation net are both made of metal material to hold the mixed alcohol solvent. The isolation net plays the role of supporting the mixed alcohol gel and isolating the lower end area, and its porous structure can also allow the volatilized mixed alcohol solvent to contact the mixed alcohol gel. The container cover is made of glass, and the through holes on the container cover are used to allow the mixed alcohol solvent to evaporate.
[0062] Specifically, the isolation net can be fixed to the container body by means of, but not limited to, snaps, stoppers or welding. The adjustment sheet includes, but is not limited to, designing the container cover to be double-layered, with the upper layer being an upper cover with through holes and the lower layer being an adjustment sheet with a shielding unit.
[0063] According to some more preferred embodiments, in order to ensure that the upper end area of the pinhole drying device can be in an environment of saturated vapor pressure after the mixed alcohol solvent is injected, the fixed position of the isolation net is limited to make the height ratio of the upper end area and the lower end area 2:8 to 5:5 (for example, it can be 2:8, 2.5:7.5, 3:7, 3.5:6.5, 4:6, 4.5:5.5 or 5:5), and the ratio of the height of the upper end area to the thickness of the mixed alcohol gel is not less than 2:1 (for example, it can be 2:1, 2.5:1, 3:1, 4:1, 5:1, etc.).
[0064] According to some preferred embodiments, the diameter of the through hole is 200-500 μm (for example, it can be 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm); the porosity on the container cover is 0.005-0.015% (for example, it can be 0.005%, 0.0055%, 0.006%, 0.0065%, 0.007%, 0.0075%, 0.008%, 0.0085%, 0.009%, 0.0095%, 0.01% or 0.015%).
[0065] In the embodiment of the present invention, it has been experimentally confirmed that if the diameter of the through hole opened on the container cover is too large or the porosity is too large, microcracks caused by the rapid volatilization of the highly volatile low-level alcohol will still occur; if the diameter of the through hole opened on the container cover is too small or the porosity is too small, the hole reconstruction efficiency will be too low.
[0066] According to some preferred embodiments, in step (3): the pinhole drying device is placed in a ventilated environment, and controllable volatilization is performed by controlling the opening and closing degree of the through holes on the container cover, the wind speed of the ventilation environment and the ambient temperature.
[0067] In the present invention, there are both large pores and small pores in the mixed alcohol gel, and the solvent in the large pores is more easily volatilized, while the solvent in the small pores is not easy to volatilize. Therefore, after the large pore solvent evaporates, the large pores will shrink. After shrinking, the mixed alcohol solvent in the lower end area of the pinhole drying device will be filled into the pores again. In this way, this process is circulated at the saturated vapor pressure, and the pore diameter of the large pores will gradually shrink, thereby realizing a pore reconstruction process in which the large pores become smaller and the small pores remain basically unchanged.
[0068] According to some preferred embodiments, in step (3): the time of controlled volatilization is 6 to 120 h (for example, it can be 6 h, 8 h, 10 h, 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, 96 h, 108 h or 120 h).
[0069] It should be noted that after the controlled volatilization for a controlled volatilization time, the volume of the mixed alcohol solvent no longer changes, and only higher alcohol remains in the lower end area of the pinhole drying device.
[0070] According to some more preferred embodiments, in step (3): the time of controlled volatilization is 48 hours.
[0071] According to some preferred embodiments, the volume of the pore-reconstructed transparent silica alcohol gel is 1 / 10 to 1 (for example, it may be 1 / 10, 1 / 9, 1 / 8, 1 / 7, 1 / 6, 1 / 5, 1 / 4, 1 / 3, 1 / 2 or 1) of the mixed alcohol gel.
[0072] According to some more preferred embodiments, the volume of the pore reconstructed transparent silica alcohol gel is 1 / 4 of that of the mixed alcohol gel.
[0073] In the present invention, the volume of the transparent silica alcohol gel with pore reconstruction is determined by limiting the volume ratio of the lower alcohol and the higher alcohol in the mixed alcohol solvent. For example, when the volume ratio of the lower alcohol and the higher alcohol is 3:1, the volume of the transparent silica alcohol gel with pore reconstruction is 1 / 4 of that of the mixed alcohol gel.
[0074] It should be noted that if the mixed alcohol gel is simply exposed to the atmosphere for liquid volatilization, the surface of the mixed alcohol gel will crack or even completely break into pieces, which will seriously affect the integrity of the final aerogel product. Therefore, in order to achieve controllable volatilization of the liquid solvent in the pores of the mixed alcohol gel while retaining the integrity of the mixed alcohol gel, three measures are taken in the present invention: ① A unique pinhole drying device is designed, which consists of a container body, an isolation net and a container cover with through holes, wherein the isolation net is fixed to the inner wall of the container body and has a certain spacing distance from the bottom of the container body, the isolation net is kept at a certain distance from the top of the container cover and ensures that it is transparent and can accommodate the mixed alcohol gel, and dense through holes are punched on the surface of the container cover to ensure that the inside and outside of the container body can be ventilated. ① Since the inside of the pinhole drying device is always in a saturated vapor pressure environment, the surface liquid of the mixed alcohol gel will not cause cracking due to local lack of liquid while evaporating; ② The evaporation rate of the liquid in the mixed alcohol gel can be controlled by controlling the wind speed, ambient temperature and the degree of opening and closing of the holes on the container cover. It should be noted that the degree of opening and closing of the holes on the container cover (the number of holes opened and closed on the cover) is the most reliable and accurate control strategy; ③ The liquid inside the mixed alcohol gel and the liquid in the lower end area of the pinhole drying device are all controlled to be a mixed alcohol solvent composed of small molecular weight lower alcohols (good volatility) and relatively large molecular weight higher alcohols (poor volatility). In addition to avoiding cracks caused by the excessive evaporation of all volatile lower alcohols in the initial stage of the alcohol gel, more importantly, the residual amount of higher alcohols with poor volatility can be accurately controlled to ensure the final volume shrinkage of the alcohol gel and thus the density of the final aerogel.
[0075] Specifically, in step (2), the mixed alcohol gel is placed on the isolation net of the pinhole drying device, and the same mixed alcohol solvent as in step (1) is injected under the isolation net to ensure that the mixed alcohol solvent covers the isolation net and contacts the bottom of the mixed alcohol gel, and then the container cover is covered, and the through hole is closed by the adjustment plate so that the container body and the container cover form a closed container, and then the pinhole drying device is sealed for at least 10 minutes before entering step (3); in step (3), the pinhole drying device containing the mixed alcohol gel in step (2) is placed in an exhaust device or a fume hood, and the wind speed, ambient temperature and the degree of opening and closing of the through hole on the container cover are controlled, and then the mixed alcohol solvent in the pinhole drying device is controllably volatilized over a period of time until the volume of the mixed alcohol solvent in the pinhole drying device no longer changes. At this time, the lower alcohol has been completely volatilized, and the mixed alcohol gel has undergone a certain degree of volume reduction, thereby obtaining a transparent silica alcohol gel with pore reconstruction.
[0076] According to some preferred embodiments, in step (4), supercritical drying is carried out by supercritical carbon dioxide drying, the pressure in the drying kettle is maintained at 8 to 20 MPa (for example, 8 MPa, 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa or 20 MPa), the temperature in the drying kettle is controlled to be 10 to 25°C (for example, 10°C, 12°C, 15°C, 16°C, 18°C, 20°C, 22°C or 25°C), and the circulating liquid carbon dioxide is used to maintain 24 to 120 hours (for example, 24 hours, 36 hours, 48 hours, 60 hours, 72 hours, 84 hours, 96 hours, 108 hours or 120 hours), and then the drying kettle is heated at 5 to 10°C / min. h (for example, it can be 5°C / h, 5.5°C / h, 6°C / h, 6.5°C / h, 7°C / h, 7.5°C / h, 8°C / h, 8.5°C / h, 9°C / h, 9.5°C / h or 10°C / h) to 40°C to reach a supercritical state and maintain it for 24 to 72 h (for example, it can be 24 h, 30 h, 36 h, 48 h, 60 h or 72 h), and then the pressure is released to atmospheric pressure at a rate of 0.3 to 1 MPa / h (for example, it can be 0.3 MPa / h, 0.4 MPa / h, 0.5 MPa / h, 0.6 MPa / h, 0.7 MPa / h, 0.8 MPa / h, 0.9 MPa / h or 1 MPa / h).
[0077] In the present invention, it is preferred to use a slower heating rate of 5 to 10°C / h to heat up to 40°C to reach a supercritical state, which can effectively avoid cracks on the surface and inside of the ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by the present invention. Experimental confirmation shows that the present invention has found that if the heating rate is too fast, it is difficult to achieve uniform temperature in the supercritical reactor, and it is also difficult to achieve uniform temperature in the transparent silica alcohol gel block with pore reconstruction, which will form a temperature gradient. This temperature gradient will further cause a stress gradient, which will form cracks on the surface of the silica aerogel and inside the block, affecting the preparation of the aerogel. At the same time, in the present invention, it is preferred to use a slower pressure release rate (0.3-1 MPa / h) to release the pressure to atmospheric pressure, which can effectively avoid cracks in the ultra-transparent, ultra-insulating, lightweight silica aerogel prepared by the present invention; this is mainly because while releasing the pressure, the temperature inside the supercritical drying kettle will also decrease. If the pressure release rate is too fast, even if the supercritical drying kettle is continued to be heated, the local temperature inside the kettle and the gel block will drop significantly at some point. While the temperature and pressure are reduced, the carbon dioxide may change from a supercritical state to a liquid state, which will eventually lead to the generation of cracks in the silica aerogel.
[0078] The present invention also provides an ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by the above-mentioned preparation method.
[0079] According to some preferred embodiments, the ultra-transparent, ultra-insulating, lightweight silica aerogel material has one or more of the following properties:
[0080] The density of ultra-transparent, ultra-insulating and lightweight silica aerogel material is 0.06-0.15 g / cm 3 ;
[0081] The ultra-transparent, ultra-insulating, lightweight silica aerogel material with a thickness of 10 mm has a light transmittance of 90.5-93.8% and a haze of 1.2-3.1% at 550 nm;
[0082] The thermal conductivity of the ultra-transparent, ultra-insulating, lightweight silica aerogel material is 0.010 to 0.014 W / (m·K) at room temperature and pressure, and is 0.012 to 0.017 W / (m·K) at 100°C and pressure.
[0083] The present invention also provides an ultra-transparent, ultra-insulating, lightweight silica aerogel material for applications such as transparent thermal insulation, high-energy particle capture, etc. in solar thermal collection systems, new generation space science fields, high-energy physics fields, building fields, or electronic fields.
[0084] Unless otherwise specified, the raw materials used in the present invention can be products that can be directly purchased on the market or synthesized by existing methods;
[0085] In the present invention, “and / or” appearing between multiple technical features means that these technical features are connected in an “and / or” relationship, indicating that it can be any one of these technical features, or a combination of any two or more of these technical features.
[0086] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0087] Example 1
[0088] (1) 15.2 g of methyl orthosilicate, 32 g of methanol, 3.6 g of water, and 10 μL of 0.1 mol / L dilute hydrochloric acid were added to a flask, mixed by magnetic stirring, heated to 70°C, refluxed at this temperature for 8 h, and the reflux device was replaced by a distillation device, the temperature was raised to 100°C, and the methanol in the reaction solution was completely evaporated. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixed solution; then, a sufficient amount of acetonitrile was added to the mixed solution to make the total mass of the mixed solution 240 g (corresponding to a final wet gel solid content of 2.5%), 1 mL of 0.3 mol / L ammonia water was added dropwise to the mixed solution, stirred evenly, and poured into a molding mold to form a gel, and then placed in a 60°C oven for 48 h. After the mold was cooled, it was taken out to obtain a transparent silica wet gel;
[0089] (2) placing the transparent silica wet gel in a solvent replacement box, pouring in a mixed alcohol solvent consisting of ethanol and n-pentanol (the volume ratio of ethanol to n-pentanol is 3:1) in an excess amount of 10 times the volume of the transparent silica wet gel, soaking for 1 to 2 days and then pouring out the waste liquid, repeating this step three times to obtain a mixed alcohol gel;
[0090] (3) Place the mixed alcohol gel into Figure 2 On the isolation net of the pinhole drying device shown, a mixed alcohol solvent composed of ethanol and n-pentanol (the volume ratio of ethanol to n-pentanol is 3:1) is injected into the lower end area of the isolation net to ensure that the mixed alcohol solvent submerges the isolation net and contacts the bottom of the mixed alcohol gel, and then the container cover is covered, and the through hole is controlled by the adjustment plate to close, so that the container body and the container cover form a closed container, and then the pinhole drying device is sealed for 1 hour; wherein, the diameter of the through hole on the container cover is 200 μm, the size of the container cover is a square of 200 mm*200 mm, and a through hole is set every 20 mm, and the porosity is 0.0078%;
[0091] (4) placing the pinhole drying device containing the mixed alcohol gel in a fume hood, controlling the wind speed to 0.1-0.5 m / s and the ambient temperature to 25° C., opening 1 / 8-1 / 4 of the total number of holes on the container cover and dynamically adjusting the openings, and then allowing the mixed alcohol solvent in the pinhole drying device to evaporate. After 48 hours, the volume of the mixed alcohol solvent at the bottom of the pinhole drying device no longer changes significantly, and the volume of the mixed alcohol gel shrinks to 1 / 4 of the initial volume, thereby obtaining a transparent silica alcohol gel with pore reconstruction (the solid content at this time is about 10%);
[0092] (5) Using a porous aluminum plate, the transparent silica alcohol gel with pore reconstruction was placed in an excess of 10 times the volume of anhydrous ethanol and soaked for 2 days. After repeated replacement twice, supercritical drying was performed. Using a porous aluminum plate, the alcohol gel replaced by ethanol solvent was carefully placed in a drying kettle, ethanol was added to cover the gel, and then liquid carbon dioxide was injected into the drying kettle, and the pressure in the kettle was maintained at 16MPa. The temperature in the drying kettle was controlled to 20°C by circulating liquid carbon dioxide, and then the temperature was raised to 40°C at a rate of 5°C / h to reach a supercritical state. At this temperature, the circulating supercritical carbon dioxide was used to continue replacement for 24h to ensure that the ethanol waste liquid was completely taken out. Then, while maintaining the temperature in the drying kettle at 40°C, the pressure was released to atmospheric pressure at a rate of 0.6MPa / h. After the temperature in the kettle dropped to room temperature, the ultra-transparent, ultra-insulating, lightweight silica aerogel material was obtained.
[0093] The density of the ultra-transparent, ultra-insulating, lightweight silica aerogel material obtained in this embodiment is 0.106 g / cm 3The thermal conductivity at room temperature is 0.0101 W / (m·K), and the thermal conductivity at 100°C and normal pressure is 0.0122 W / (m·K). The appearance of the ultra-transparent, ultra-insulating, lightweight silica aerogel prepared in this embodiment is shown in FIG. Figure 3 As shown, it can be seen that the transparency of the silica aerogel prepared in this embodiment is extremely high, and the light transmittance at 550nm is tested to be 93.8%, and the haze is 1.2%; the transmission electron microscope image of the ultra-transparent, ultra-insulating and lightweight silica aerogel prepared in this embodiment of the present invention is as follows Figure 4 The scanning electron microscope image is shown in Figure 5 As shown, from Figure 5 It can be seen that the nanoparticles and nanopores of silica aerogel are very small and show very good uniformity.
[0094] Example 2
[0095] Embodiment 2 is substantially the same as Embodiment 1, except that:
[0096] In step (1), 15.2 g of methyl orthosilicate, 32 g of methanol, 3.6 g of water, and 10 μL of 0.1 mol / L dilute hydrochloric acid are added to a flask, mixed by magnetic stirring, heated to 70° C., refluxed at this temperature for 8 h, the reflux device is replaced by a distillation device, the temperature is raised to 100° C., the methanol in the reaction solution is completely evaporated, and the reaction is cooled to room temperature after completion of the reaction to obtain a mixed solution; then, a sufficient amount of acetonitrile is added to the mixed solution to make the total mass of the mixed solution 600 g (corresponding to a final wet gel solid content of 1%), 1 mL of 0.3 mol / L ammonia water is added dropwise to the mixed solution, stirred evenly, and poured into a molding mold for gelation, and then placed in a 60° C. oven for 48 h, and the mold is taken out after cooling to obtain a transparent silica wet gel;
[0097] In step (2) and step (3), a mixed alcohol solvent consisting of ethanol and n-pentanol in a volume ratio of 9:1 is selected, so that after step (4), a transparent silica gel with pore reconstruction whose volume is reduced to 1 / 10 of the initial volume is obtained (the solid content is about 10% at this time).
[0098] Example 3
[0099] Embodiment 3 is substantially the same as Embodiment 1, except that:
[0100] In step (1), 15.2 g of methyl orthosilicate, 32 g of methanol, 3.6 g of water, and 10 μL of 0.1 mol / L dilute hydrochloric acid are added to a flask, mixed by magnetic stirring, heated to 70° C., refluxed at this temperature for 8 h, the reflux device is replaced by a distillation device, the temperature is raised to 100° C., the methanol in the reaction solution is completely evaporated, and after the reaction is completed, the mixture is cooled to room temperature to obtain a mixed solution; then, a sufficient amount of acetonitrile is added to the mixed solution to make the total mass of the mixed solution 62.5 g (corresponding to a final wet gel solid content of 9.6%), 1 mL of 0.3 mol / L ammonia water is added dropwise to the mixed solution, stirred evenly, and poured into a molding mold to form a gel, which is then placed in a 60° C. oven for 48 h, and the mold is taken out after cooling to obtain a transparent silica wet gel;
[0101] In step (2) and step (3), a mixed alcohol solvent consisting of ethanol and n-pentanol in a volume ratio of 0.0416:1 is selected, so that after step (4), a transparent silica gel with pore reconstruction (solid content at this time is about 10%) is obtained.
[0102] Example 4
[0103] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0104] In step (3), the diameter of the through hole on the container cover is 500 μm, the size of the container cover is a square of 200 mm*200 mm, and one through hole is set every 50 mm, with a porosity of 0.0078%.
[0105] Example 5
[0106] Example 5 is substantially the same as Example 1, except that:
[0107] In step (3), the diameter of the through hole on the container cover is 200 μm, the size of the container cover is a square of 200 mm*200 mm, and one through hole is set every 25 mm, with a porosity of 0.005%.
[0108] Example 6
[0109] Embodiment 6 is substantially the same as Embodiment 1, except that:
[0110] In step (3), the diameter of the through hole on the container cover is 200 μm, the size of the container cover is a square of 200 mm*200 mm, and a through hole is set every 14.5 mm, with a porosity of 0.015%.
[0111] Example 7
[0112] Example 7 is substantially the same as Example 1, except that:
[0113] In step (4), the pinhole drying device containing the mixed alcohol gel is placed in a fume hood, the wind speed is controlled to be 0.1-0.5 m / s and the ambient temperature is 25°C, 1 / 8-1 / 4 of the total number of holes on the container cover are opened and dynamically adjusted, and then the mixed alcohol solvent in the pinhole drying device is allowed to evaporate. After 6 hours, the volume of the mixed alcohol solvent at the bottom of the pinhole drying device no longer changes significantly, and the volume of the mixed alcohol gel is reduced to 1 / 4 of the initial volume, thereby obtaining a transparent silica alcohol gel with pore reconstruction (the solid content is about 10% at this time).
[0114] Example 8
[0115] Example 8 is substantially the same as Example 1, except that:
[0116] In step (2) and step (3), a mixed alcohol solvent consisting of ethanol and n-pentanol in a volume ratio of 4:1 is selected, so that after step (4), a transparent silica gel with pore reconstruction is obtained, the volume of which is reduced to 1 / 5 of the initial volume (the solid content is about 12.5% at this time).
[0117] Comparative Example 1
[0118] (1) 15.2 g of methyl orthosilicate, 32 g of methanol, 3.6 g of water, and 10 μL of 0.1 mol / L dilute hydrochloric acid were added to a flask, mixed by magnetic stirring, heated to 70°C, refluxed at this temperature for 8 h, and the reflux device was replaced by a distillation device, the temperature was raised to 100°C, and the methanol in the reaction solution was completely evaporated. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixed solution; then, a sufficient amount of acetonitrile was added to the mixed solution to make the total mass of the mixed solution 240 g (corresponding to a final wet gel solid content of 2.5%), 1 mL of 0.3 mol / L ammonia water was added dropwise to the mixed solution, stirred evenly, and poured into a molding mold to form a gel, and then placed in a 60°C oven for 48 h. After the mold was cooled, it was taken out to obtain a transparent silica wet gel;
[0119] (2) Using a porous aluminum plate, the transparent silica wet gel is placed in anhydrous ethanol with a volume of 10 times excess for 2 days, and the solution is replaced twice before supercritical drying. Using a porous aluminum plate, the wet gel replaced by the ethanol solvent is carefully placed in a drying kettle, ethanol is added to cover the gel, and then liquid carbon dioxide is injected into the drying kettle, the pressure in the kettle is maintained at 16MPa, and the temperature in the drying kettle is controlled to be 20°C by circulating liquid carbon dioxide, and then the temperature is raised to 40°C at a rate of 5°C / h to reach a supercritical state, and at this temperature, the circulating supercritical carbon dioxide is used to continue to replace for 24h to ensure that the ethanol waste liquid is completely removed, and then the temperature in the drying kettle is maintained at 40°C, and the pressure is released to atmospheric pressure at a rate of 0.6MPa / h, and the aerogel material is obtained after the temperature in the kettle drops to room temperature.
[0120] Comparative Example 2
[0121] Comparative Example 2 is substantially the same as Example 1, except that:
[0122] In step (3), only one 3.12 mm 2 The through hole of the container cover is 200mm*200mm square, and the porosity is 0.0078%;
[0123] In step (4), the pinhole drying device containing the mixed alcohol gel is placed in a fume hood, the wind speed is controlled to be 0.1-0.5 m / s and the ambient temperature is 25°C, the hole on the container cover is opened, and then the mixed alcohol solvent in the pinhole drying device is allowed to evaporate. After 36 hours, the volume of the mixed alcohol solvent at the bottom of the pinhole drying device no longer changes significantly, and the volume of the mixed alcohol gel is reduced to 1 / 4 of the initial volume, thereby obtaining a transparent silica alcohol gel with pore reconstruction (the solid content is about 10% at this time).
[0124] Comparative Example 3
[0125] Comparative Example 3 is substantially the same as Example 1, except that:
[0126] In step (4), the pinhole drying device containing the mixed alcohol gel is placed in a fume hood, the wind speed is controlled to be 0.1-0.5 m / s and the ambient temperature is 50°C, 1 / 8-1 / 4 of the total number of holes on the container cover are opened and dynamically adjusted, and then the mixed alcohol solvent in the pinhole drying device is allowed to evaporate. After 4 hours, the volume of the mixed alcohol solvent at the bottom of the pinhole drying device no longer changes significantly, and the volume of the mixed alcohol gel is reduced to 1 / 4 of the initial volume, thereby obtaining a transparent silica alcohol gel with pore reconstruction (the solid content is about 10% at this time).
[0127] Comparative Example 4
[0128] Comparative Example 4 is substantially the same as Example 1, except that:
[0129] The pinhole drying device containing the mixed alcohol gel is placed in a fume hood, the wind speed is controlled at 1-2 m / s and the ambient temperature is 25°C, 1 / 8-1 / 4 of the total number of holes on the container cover are opened and dynamically adjusted, and then the mixed alcohol solvent in the pinhole drying device is allowed to evaporate. After 2 hours, the volume of the mixed alcohol solvent at the bottom of the pinhole drying device no longer changes significantly, and the volume of the mixed alcohol gel is reduced to 1 / 4 of the initial volume, thereby obtaining a transparent silica alcohol gel with pore reconstruction (the solid content is about 10% at this time).
[0130] The ultra-transparent, ultra-insulating, lightweight silica aerogel materials prepared in Examples 1 to 8 and the aerogel materials prepared in Comparative Examples 1 to 4 were used as products, and performance tests were performed on these products to obtain performance indicators as shown in Table 1.
[0131] Table 1
[0132]
[0133]
[0134] It should be noted that the light transmittances are all the light transmittances of products with a thickness of 10 mm measured at 550 nm.
[0135] As shown in Table 1, the density of the ultra-transparent, ultra-insulating and lightweight silica aerogel materials prepared in Examples 1 to 7 is lower than 0.15 g / cm 3 , its transmittance is 92.4-93.8%, and its haze is 1.2-2.4%; and its thermal conductivity is not higher than 0.014W / (m·K) at room temperature and normal pressure, and its thermal conductivity is not higher than 0.017W / (m·K) at 100℃ and normal pressure, and the solid content of the aerogel material is 10%, and its thermal conductivity is significantly better than the aerogel material with a solid content of 12.5% in Example 8. Comparative Example 1 did not perform a pore reconstruction process on the transparent silica wet gel. There are both large and small pores inside the aerogel, so the thermal conductivity at room temperature and 100℃ is higher, its transmittance is lower, and the haze is higher. Comparative Example 2 uses a pinhole drying device with only one through hole. Because the size of the through hole is too large, the lower alcohol evaporates faster during the pore reconstruction process, and the pores in the final aerogel have poor uniformity, resulting in slightly poor thermal insulation performance, low transmittance, and high haze. Comparative Examples 3 and 4 regulated the ambient temperature and wind speed, resulting in a greatly shortened controllable volatilization time. Therefore, the reduction degree of the macropores during the pore reconstruction process was uneven, and the volatilization rate of the low-level alcohol was too fast. The size of the macropores after reconstruction was still large, resulting in the final aerogel product having poor thermal insulation performance, low transmittance, and high haze.
[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. The parts not described in detail in the present invention are well-known technologies of those skilled in the art.
Claims
1. A method for preparing an ultra-transparent, ultra-insulating, lightweight silica aerogel material, characterized in that: include: (1) soaking a transparent silica wet gel having a silica solid content of 1 to 10% in a mixed alcohol solvent for solvent replacement to obtain a mixed alcohol gel; wherein the mixed alcohol solvent is composed of lower alcohols and higher alcohols with different molecular weights; (2) placing the mixed alcohol gel on a separation net in a pinhole drying device, and injecting the mixed alcohol solvent into the pinhole drying device until the mixed alcohol solvent contacts the mixed alcohol gel through the separation net, and sealing the pinhole drying device; (3) volatilizing the mixed alcohol solvent in the pinhole drying device in a controllable manner until the volume of the mixed alcohol solvent no longer changes, thereby obtaining a transparent silica alcohol gel with pore reconstruction; (4) The transparent silica alcohol gel with reconstructed pores is subjected to ethanol solvent replacement and supercritical drying in sequence to obtain an ultra-transparent, ultra-insulating and lightweight silica aerogel material.
2. The preparation method according to claim 1, characterized in that: The transparent silicon dioxide wet gel has a silicon dioxide solid content of 2.5%.
3. The preparation method according to claim 1, characterized in that: The lower alcohol is one or more of methanol, ethanol, propanol, isopropanol, butanol, isobutanol, preferably ethanol; the higher alcohol is one or more of n-pentanol, isopentanol, n-hexanol, heptanol, octanol, ethylene glycol, hexanetriol, preferably n-pentanol; and / or, The volume ratio of the lower alcohol to the higher alcohol is (0.01-9):1, preferably 3:
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The pinhole drying device includes a container body, an isolation net and a container cover; the isolation net is fixed inside the container body to divide the pinhole drying device into an upper end area and a lower end area; the mixed alcohol gel is placed on the isolation net, and the mixed alcohol solvent is placed in the lower end area; a through hole is opened on the container cover, and an adjustment sheet for adjusting the opening and closing of the through hole is provided on the container cover; when the adjustment sheet controls the closing of the through hole, the container body and the container cover form a closed container.
5. The preparation method according to claim 4, characterized in that: The diameter of the through hole is 200-500 μm; the porosity of the container cover is 0.005-0.015%.
6. The preparation method according to claim 4, characterized in that: In step (3): Placing the pinhole drying device in a ventilated environment, and performing controllable volatilization by controlling the opening and closing degree of the through hole on the container cover, the wind speed of the ventilated environment and the ambient temperature; and / or, The controlled volatilization time is 6 to 120 hours, preferably 48 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The volume of the pore-reconstructed transparent silica alcohol gel is 1 / 10 to 1, preferably 1 / 4, of the mixed alcohol gel.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (4): The supercritical drying adopts supercritical carbon dioxide drying, maintains the pressure in the drying kettle at 8-20MPa, controls the temperature in the drying kettle at 10-25°C, maintains it for 24-120h by circulating liquid carbon dioxide, then raises the temperature to 40°C at a rate of 5-10°C / h to reach a supercritical state and maintains it for 24-72h, and then releases the pressure to atmospheric pressure at a rate of 0.3-1MPa / h.
9. An ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by the preparation method according to any one of claims 1 to 8; preferably, the ultra-transparent, ultra-insulating, lightweight silica aerogel material has one or more of the following properties: The ultra-transparent, ultra-insulating, lightweight silica aerogel material has a density of 0.06 to 0.15 g / cm 3 ; The ultra-transparent, ultra-insulating, lightweight silica aerogel material with a thickness of 10 mm has a light transmittance of 90.5-93.8% and a haze of 1.2-3.1% at 550 nm; The thermal conductivity of the ultra-transparent, ultra-insulating, lightweight silica aerogel material is 0.010-0.014 W / (m·K) at room temperature and pressure, and the thermal conductivity is 0.012-0.017 W / (m·K) at 100° C. and pressure.
10. An application of an ultra-transparent, ultra-insulating, lightweight silica aerogel material prepared by the preparation method described in any one of claims 1 to 8 in solar thermal collection systems, new generation space science fields, high energy physics fields, building fields or electronic fields.
Citation Information
Patent Citations
Low-density transparent silica aerogel and preparation method
CN105271263A
Blocky transparent silica aerogel, and rapid preparation method and application thereof
CN109019611A
Enhanced type transparent silicon dioxide aerogel and preparation method thereof
CN109179428A
Efficient heat-insulating light transparent silicon dioxide aerogel material and preparation method thereof
CN117699808A
Preparation of silica aerogel
KR1019990009158A